Recent progress in the development of advanced support materials for electrocatalysis - Smiljanić, M.; Srejić, I.; Georgijević, J. P.; Maksić, A.; Bele, M.; Hodnik, N. (Frontiers in Chemistry, 2023)
Electrocatalytic materials are pivotal for clean chemical production and energy conversion in devices like electrolyzers and fuel cells. These materials usually consist of metallic nanoparticles which serve as active reaction sites, and support materials which provide high surface area, conductivity and stability. When designing novel electrocatalytic composites, the focus is often on the metallic sites, however, the significance of the support should not be overlooked. Carbon materials, valued for their conductivity and large surface area, are commonly used as support in benchmark electrocatalysts. However, using alternative support materials instead of carbon can be beneficial in certain cases. In this minireview, we summarize recent advancements and key directions in developing novel supports for electrocatalysis, encompassing both carbon and non-carbon materials.